2007
DOI: 10.1021/es0606780
|View full text |Cite
|
Sign up to set email alerts
|

Application of Land Use Regression to Estimate Long-Term Concentrations of Traffic-Related Nitrogen Oxides and Fine Particulate Matter

Abstract: Land use regression (LUR) is a promising technique for predicting ambient air pollutant concentrations at high spatial resolution. We expand on previous work by modeling oxides of nitrogen and fine particulate matter in Vancouver, Canada, using two measures of traffic. Systematic review of historical data identified optimal sampling periods for NO and N02. Integrated 14-day mean concentrations were measured with passive samplers at 116 sites in the spring and fall of 2003. Study estimates for annual mean NO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
393
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 466 publications
(410 citation statements)
references
References 23 publications
12
393
3
2
Order By: Relevance
“…By means of establishing a statistical relationship between pollutant concentrations measured at 20-100 sites and potential influencing factors such as land use, traffic, and population density, LUR is able to predict concentrations at unsampled locations throughout a given domain within the framework of GIS (Henderson et al 2007;Hoek et al 2008). LUR has achieved great success in predicting concentrations of major air pollutants, mainly in Europe and North America (Hoek et al 2008), yet it has seldom been applied to China (Li et al 2010a, b), one of the most seriously air-polluted regions in the world.…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
See 3 more Smart Citations
“…By means of establishing a statistical relationship between pollutant concentrations measured at 20-100 sites and potential influencing factors such as land use, traffic, and population density, LUR is able to predict concentrations at unsampled locations throughout a given domain within the framework of GIS (Henderson et al 2007;Hoek et al 2008). LUR has achieved great success in predicting concentrations of major air pollutants, mainly in Europe and North America (Hoek et al 2008), yet it has seldom been applied to China (Li et al 2010a, b), one of the most seriously air-polluted regions in the world.…”
Section: Responsible Editor: Gerhard Lammelmentioning
confidence: 99%
“…In the absence of traffic intensity data, we used the length of specific road types as a reasonable proxy (Henderson et al 2007). Some studies (Dong et al 2014;Feng et al 2013) have shown that average traffic volume on major roads in Beijing is 97 vehicle/km, which is close to volume in the study implemented in New York (Ross et al 2007).…”
Section: Development Of Predictor Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Jerrett et al (2005b) review several exposure modeling approaches that may be useful for specific traffic-related pollutants that exhibit strong gradients within urban areas, such as in congested urban centers or downwind of major highways. One such modeling approach currently receiving attention is ''land-use regression'' (Henderson et al, 2007;Jerrett et al, 2007;Moore et al, 2007;Rosenlund et al, 2007a), a method intended to predict local variations in specific air quality measures by implicitly accounting for the types of local sources and sinks typically found within a city. However, each type of pollution source (traffic, space heating, major industrial point sources) is characterized by a different group of co-emitted pollutants, so that although the resulting spatial map of the target pollutant is intended to represent that pollutant (alone), it actually includes all of the copollutants for the mix of source types involved.…”
Section: Exposures Based On ''Traffic-related'' Ambient Air Qualitymentioning
confidence: 99%